2021
DOI: 10.3390/cancers13133138
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Is Correlated with Oxidative Stress in Myelodysplastic Syndrome—Relevance as Complementary Prognostic Biomarkers

Abstract: Oxidative stress and abnormal DNA methylation have been implicated in cancer, including myelodysplastic syndromes (MDSs). This fact leads us to investigate whether oxidative stress is correlated with localized and global DNA methylations in the peripheral blood of MDS patients. Sixty-six MDS patients and 26 healthy individuals were analyzed. Several oxidative stress and macromolecule damage parameters were analyzed. Localized (gene promotor) and global DNA methylations (5-mC and 5-hmC levels; LINE-1 methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Our findings detected an association between TAC and MPNs (OR = 1.82; p = 0.05), particularly in ET (OR = 2.36; p = 0.03) and PMF (OR = 2.11; p = 0.03), reinforcing the idea that derangements in the pro-oxidant/antioxidant equilibrium might trigger the onset of myeloid malignancies, e.g., MPNs, MDS, AML, and others, as previously hypothesized [27,28].…”
Section: Discussionsupporting
confidence: 76%
“…Our findings detected an association between TAC and MPNs (OR = 1.82; p = 0.05), particularly in ET (OR = 2.36; p = 0.03) and PMF (OR = 2.11; p = 0.03), reinforcing the idea that derangements in the pro-oxidant/antioxidant equilibrium might trigger the onset of myeloid malignancies, e.g., MPNs, MDS, AML, and others, as previously hypothesized [27,28].…”
Section: Discussionsupporting
confidence: 76%
“…2C ). It is known that the promoters with CpG island are the target for DNA methylation, and the methylation status regulates the expression of genes [ 50 ]. Increasing studies have shown that the magnitude of oxidative stress alters methylation/demethylation patterns of genes and their expression [ 45 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer models treated with vitamin E exhibit decreased DNMT protein expression and reduced CpG methylation at target loci of genes involved in cellular redox homeostasis such as the Nrf2 promoter (Huang et al, 2012a). As oxidative stress is often correlated with increased global levels of 5mC (Garcia-Guede et al, 2020;Goncalves et al, 2021), it is possible that vitamin E can reduce DNA methylation indirectly due to its antioxidant activity (Ryan et al, 2010;Zappe et al, 2018).…”
Section: Indirect Micronutrient Regulation Of Dna Methylationmentioning
confidence: 99%